Development Of Students' Cognitive Skills Through Ecological Education In Preschool Educational Organizations - Qurbanova, Asal (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article discusses the issues of providing environmental education in preschool educational organizations, the effectiveness of providing environmental education, instilling a love for nature through the development of environmental education, preserving nature, the interaction between humans and nature, ways of introducing nature, forming a positive attitude of students towards nature, and expanding their knowledge of its phenomena and laws.